Impacts of fullerene C60 and virgin olive oil on cadmium-induced genotoxicity in rats - Aly, Fayza M.; Kotb, Ahmed M.; Haridy, Mohie A. M.; Hammad, Seddik (The science of the total environment, 2018)
Currently, cadmium is considered to be one of the major environmental pollutants. Environmentally, cadmium is released in various forms e.g. oxide, chloride and sulphide. The aim of the present study was to examine the genotoxic impact of fullerene nanoparticles C60 (C60) and virgin olive oil (VOO) on cadmium chloride (CdCl2)-induced genotoxicity in rats. To evaluate these effects on DNA damage and chromosomal frequency, 25 albino rats were randomly assigned to 5 groups (n=5 per group): Group 1 served as a control; Group 2 received a single intraperitoneal dose of CdCl2 (3.5mg/kg); Group 3 animals were treated with C60 (4mg/kg, orally) every other day for 20days; Group 4 received a single intraperitoneal dose of CdCl2 (3.5mg/kg) and an oral dose of C60 (4mg/kg); and Group 5 received a single intraperitoneal dose of CdCl2 (3.5mg/kg) and oral doses of VOO every other day for 20 consecutive days. Genotoxic and anti-genotoxic effects of C60 and VOO were evaluated in the liver, kidney and bone marrow using molecular and cytogenetic assays. As expected, CdCl2 and C60 administration was associated with band number alterations in both liver and kidney; however, C60 pretreatment recovered to approximately basal number. Surprisingly, C60 and VOO significantly attenuated the genotoxic effects caused by CdCl2 in livers and kidneys. In bone marrow, in addition to a reduction in the chromosomal number, several chromosomal aberrations were caused by CdCl2. These chromosomal alterations were also reversed by C60 and VOO. In conclusion, molecular and cytogenetic studies showed that C60 and VOO exhibit anti-genotoxic agents against CdCl2-induced genotoxicity in rats. Further studies are needed to investigate the optimal conditions for potential biomedical applications of these anti-genotoxic agents.
Im Titel ist die Zahl 60 tiefgestellt
Gesehen am 08.05.2020